1991
DOI: 10.1182/blood.v77.6.1313.1313
|View full text |Cite
|
Sign up to set email alerts
|

Protection from arabinofuranosylcytosine and n-mustard-induced myelotoxicity using hemoregulatory peptide pGlu-Glu-Asp-Cys-Lys monomer and dimer

Abstract: We have previously shown that the synthetic peptide pGlu-Glu-Asp-Cys- Lys (pEEDCK monomer) inhibits the cytostatic drug-induced proliferation of hematopoietic stem cells CFU-S. Keeping CFU-S quiescent by pEEDCK treatment renders them insensitive to cycle-specific cytostatic drugs and leads to reduced toxicity. Here we show that pEEDCK application during repeated (twice) administration of clinically relevant (nonlethal) 1-beta-D-arabinofuranosylcytosine (Ara-C) doses reduced the percentage of CFU-S in S-phase f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…However, the restricted effect of some of these factors on a specific cell lineage, and the decrease in their therapeutic effect after multiple courses of chemotherapy, suggest the necessity of alternative approaches. In mice, inhibitory factors able to maintain the stem cell and early progenitor compartments in a quiescent state have been shown to exert a protective effect against myelotoxic agents (Carde et al, 1993;Dunlop et al, 1992;Grzegorzewski et al, 1995;Paukovits et al, 1990Paukovits et al, , 1991. In particular, the tetrapeptide N-acetyl-Ser-Asp-Lys-Pro (AcSDKP), now termed Goralatide, a known inhibitor of stem cells (Lenfant et al, 1989;Frindel & Monpezat, 1989), has been shown to be able to protect mice against the toxicity of high doses of chemotherapy (Bogden et al, 1991;Guigon et al, 1982).…”
mentioning
confidence: 99%
“…However, the restricted effect of some of these factors on a specific cell lineage, and the decrease in their therapeutic effect after multiple courses of chemotherapy, suggest the necessity of alternative approaches. In mice, inhibitory factors able to maintain the stem cell and early progenitor compartments in a quiescent state have been shown to exert a protective effect against myelotoxic agents (Carde et al, 1993;Dunlop et al, 1992;Grzegorzewski et al, 1995;Paukovits et al, 1990Paukovits et al, , 1991. In particular, the tetrapeptide N-acetyl-Ser-Asp-Lys-Pro (AcSDKP), now termed Goralatide, a known inhibitor of stem cells (Lenfant et al, 1989;Frindel & Monpezat, 1989), has been shown to be able to protect mice against the toxicity of high doses of chemotherapy (Bogden et al, 1991;Guigon et al, 1982).…”
mentioning
confidence: 99%
“…PEEDCK has the capability of inhibiting myelopoiesis and bears a striking similarity to a 5-amino acid sequence in the effector domain of the alphasubunit of inhibitory G-proteins (73). While the dimerized peptide indirectly stimulates hematopoiesis in vitro (74), Paukovits and others have used the monomeric peptide to protect hematopoietic progenitors from damaging chemotherapeutic effect (75). Noting that the peptide appeared to be cytostatic towards CFU-S, perhaps having a physiologic role in the maintenance of low levels of CFU-S proliferation and the ability of pEEDCK to prevent ARA-C-induced cycling of CFU-S, he and co-investigators administered peptide to mice which then were given ARA-C and nitrogen-mustard (75).…”
Section: Accelerated Cycling At the Expense Of Self-renewalmentioning
confidence: 99%
“…While the dimerized peptide indirectly stimulates hematopoiesis in vitro (74), Paukovits and others have used the monomeric peptide to protect hematopoietic progenitors from damaging chemotherapeutic effect (75). Noting that the peptide appeared to be cytostatic towards CFU-S, perhaps having a physiologic role in the maintenance of low levels of CFU-S proliferation and the ability of pEEDCK to prevent ARA-C-induced cycling of CFU-S, he and co-investigators administered peptide to mice which then were given ARA-C and nitrogen-mustard (75). Mice receiving both peptide and cytotoxic agent endured far less severe neutropenia and had preservation or enhancement of progenitor cell activity at the CFU-S and CFU-GM differentiative level.…”
Section: Accelerated Cycling At the Expense Of Self-renewalmentioning
confidence: 99%
“…This has been purified to homogeneity revealing the sequence pEEDCK (Paukovits & Laerum 1982). This peptide appears to act through a protease sensitive membrane receptor (Paukovits & Paukovits 1975) and is active in inhibiting murine and human myelomonocyticrestricted progenitor cells, the granulocyte/macrophage colony-forming cells (GM-CFC) as well as CFU-S and Long-term culture initiating cells (Paukovits et al 1990(Paukovits et al , 1991(Paukovits et al , 1993. Inhibitory activity is observed at 10-13 M however, the dose response is biphasic and inhibitory properties are lost at higher concentrations.…”
Section: Inhibitors Of Stem Cell Proliferationmentioning
confidence: 99%